Online teaching learning during COVID-19 pandemic : perception and challenges faced by teachers - Subba, Ramesh; Subba, Hem Kumari (Journal of Physiological Society of Nepal, 2021)
Introduction: Online teaching can play a vital role in the process of teaching and learning during COVID-19 pandemic. However, teachers’ perceptions and challenges are major factors in the adoption and effectiveness of online teaching learning, especially at institutions where it is newly adopted. This study aimed to investigate the perception and challenges faced by nursing teachers regarding online teaching learning during the pandemic in Bharatpur, Chitwan. Materials and methods: A web-based cross-sectional survey was undertaken among 162 nursing teachers of different nursing colleges of Chitwan actively involved in online teaching learning for undergraduate and postgraduate programs during the pandemic. Non-probability enumerative sampling technique was used to select the sample. A structured questionnaire consisting of 23 items (5-point Likert scale) covering four domains for teachers perception (usefulness, ease of use, system use and behavioral intention toward online teaching learning) was distributed to the teachers using Google Form from 2021 June 5th to 2021 July 20th. Collected data were analyzed using descriptive and inferential statistics. Results: More than half (56.2%) of the teachers had good perception towards online teaching learning during COVID 19 pandemic. Teachers faced challenges to implement online teaching learning such as poor internet connection, electricity problem, difficult to assemble all the students for the class, difficult for interaction with students, and lack of information technology skills. Conclusions: Despite having to confront numerous challenges in the online teaching process, teachers can demonstrate the positive perception toward technology of online teaching. Teachers need to be equipped with e-learning technology for effectiveness of online teaching classes.